Femtosecond Laser‐Texturing the Surface of Ti‐Based Implants to Improve Their Osseointegration Capacity. Issue 31 (14th September 2022) - Lackington, William A.; Schweizer, Peter; Khokhlova, Mariya; Cancellieri, Claudia; Guimond, Stefanie; Chopard‐Lallier, Anne‐Lise; Hofstetter, Joëlle; Schmutz, Patrik; Maeder, Xavier; Rottmar, Markus
Abstract: In modern oral maxillofacial surgery, long‐term implant stability is intrinsically linked to the quality of osseointegration. While the osseointegration capacity of implants can be improved by modifying their surface properties, commonly used techniques, including sandblasting and acid etching, are stochastic processes offering virtually zero capacity to control the uniformity and reproducibility of micro‐ and nano‐scale surface features. In this study, titanium‐aluminium‐vanadium (TiAlV) implant surfaces are modified using femtosecond (fs) laser‐texturing, and its influence on physicochemical properties, on blood–implant interactions, and on the osseointegration potential is investigated in vitro. Laser‐texturing enables the production of designer surfaces with micro‐scale features defined in size and arrangement. While state of the art TiAlV surfaces prepared by sandblasting with biphasic calcium phosphate (BCP) show significant grain refinement at the near surface, fs laser‐texturing preserves the grain size and enhances the microstrain and oxide layer thickness but also leads to 15% lower bulk fatigue in comparison to BCP treatment. Blood coagulation is similar on laser‐textured and BCP surfaces, as is mineralization by human bone progenitor cells, albeit with a decreasing trend for laser‐textured surfaces. Laser‐texturing thus presents as a promising approach to create highly reproducible designer surfaces with biological performance comparable to state‐of‐the‐art implants. Abstract : Femtosecond laser‐texturing can produce TiAlV implant surfaces with designer micro‐scale features defined in size and arrangement, while near‐surface features, including grain size, microstrain, and oxide layer thickness are shown to be modulated by the process. Laser‐textured surfaces support in vitro mineralization by bone progenitor cells, similar to current state‐of‐the‐art sandblasted and acid‐etched surfaces.